2022
DOI: 10.20517/wecn.2022.04
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in water, from treatment process to drinking water: analytical methods and potential health effects

Abstract: Aim: The commonly used analytical methods for microplastic (MPs) detection in drinking water and the threat of MP pollution in water intended for human consumption to human beings are presented through a systematic review. Furthermore, MP occurrence, transport, and fate from raw to treated drinking water, tap water, and bottled water, as well as the possible health impacts of MPs on human beings, are also evaluated. Methods: Systematic review included articles published in scientific journals that contain spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Most of the studies were published from 2017 onwards, with the highest number of publications reported in 2023 at 72 articles [Figure 3]. This is also consistent with the timeline of when the term "microplastics" became very significant in the regional context due to the information from [47] . It is important to highlight that, within the context of this analysis, the inclusion of alternative keywords such as "plastic particles" was not taken into account due to their failure to adhere to the specified size parameters for microplastics.…”
Section: Recovery Articles and Data Extractedsupporting
confidence: 75%
See 1 more Smart Citation
“…Most of the studies were published from 2017 onwards, with the highest number of publications reported in 2023 at 72 articles [Figure 3]. This is also consistent with the timeline of when the term "microplastics" became very significant in the regional context due to the information from [47] . It is important to highlight that, within the context of this analysis, the inclusion of alternative keywords such as "plastic particles" was not taken into account due to their failure to adhere to the specified size parameters for microplastics.…”
Section: Recovery Articles and Data Extractedsupporting
confidence: 75%
“…These activities can contribute to the introduction of microplastics into aquatic ecosystems. Additionally, Southeast Asia has some of the highest rates of marine plastic pollution in the world; estimates place the combined contributions of Indonesia (10%), the Philippines (6%), Vietnam (6%), Thailand (3%), and Malaysia (3%) to the world's oceans at 30% [47][48][49] . Four different types of matrices were included in this study, comprising biota, sediment, water, and others [Supplementary Table 1].…”
Section: Study Areamentioning
confidence: 99%
“…Microplastics have been detected in water supply sources, tap water, and bottled water around the world. 8,9 Microplastics contaminate the water supply system (WSS) due to numerous reasons, including the existing social systems' policies and consumptive behaviors, and limitations in treatment. The fate and transport of microplastics through the water supply cycle (WSC) are varied, and thus the timeframes and implications also range greatly depending on the entry and exit points.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study estimated that we could be ingesting cumulatively 0.1 to 5 g of microplastics a week from a combination of sources, including from drinking water which is a fundamental need for survival. Microplastics have been detected in water supply sources, tap water, and bottled water around the world. , …”
Section: Introductionmentioning
confidence: 99%
“…For drinking water samples, the sample preparation may comprise vacuum filtration, digestion, and density separation, in different combinations according to the characteristics of the matrix (Picó et al 2022). Generally, the filters employed in the first step of the sample preparation are those employed during the sampling .…”
Section: Sample Preparationmentioning
confidence: 99%